Is blood flow restriction training beneficial for athletes? - Bagley, J. R.; Rosengarten, J. J.; Galpin, A. J. (Strength and Conditioning Journal, 2015)
Blood flow restriction (bfr) training involves using specialized straps to intentionally reduce circulation (occlude) to exercising muscles. The addition of bfr to standard training approaches results in greater muscle hypertrophy and performance improvements in untrained and clinical populations. However, its implications in healthy athletes have not been reviewed. The aim of this article is to provide a concise overview of the practicality of bfr training for athletic performance. Although initial findings show promise, bfr training is relatively new and more research is needed to establish specific recommendations for volume, intensity, frequency, exercise selection, duration, and strap pressure.